2016
DOI: 10.1053/j.ajkd.2015.11.020
|View full text |Cite
|
Sign up to set email alerts
|

Red Cell Distribution Width and Mortality in Hemodialysis Patients

Abstract: BACKGROUND Red cell distribution width (RDW) is an index of red blood cell volume variability that has historically been used as a marker of iron-deficiency anemia. More recently, studies have shown that elevated RDW is associated with higher mortality risk in the general population. However, there is lack of data demonstrating the association between RDW and mortality risk in hemodialysis (HD) patients. We hypothesized that higher RDW levels are associated with higher mortality in HD patients. STUDY DESIGN … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

5
79
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 76 publications
(85 citation statements)
references
References 27 publications
5
79
1
Order By: Relevance
“…In this study, the significant correlations, though weak, with dialysis vintage, nutritional and inflammatory factors observed were consistent with the previous findings in dialysis patients [12,14,15,34,38] . Besides, patients with higher RDW were more likely to be older and belonged to the female gender.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…In this study, the significant correlations, though weak, with dialysis vintage, nutritional and inflammatory factors observed were consistent with the previous findings in dialysis patients [12,14,15,34,38] . Besides, patients with higher RDW were more likely to be older and belonged to the female gender.…”
Section: Discussionsupporting
confidence: 93%
“…Besides, patients with higher RDW were more likely to be older and belonged to the female gender. The relation between RDW and ageing has been convincingly reported in many literatures, while its relation with gender was controversial [38] . Some studies found no significant gender differences in RDW values.…”
Section: Discussionmentioning
confidence: 99%
“…noted a positive correlation between malnutrition and RDW in a cohort of 1293 patients receiving peritoneal dialysis and observed that RDW emerged as an independent predictor of cardiovascular mortality [35]. Similar associations were also observed in patients receiving hemodialysis and kidney transplant recipients [12, 13, 25]. In this study, we found that RDW was negatively correlated with the levels of malnutrition parameters (albumin, prealbumin and serum triglyceride), showing that undernutrition may be associated with increases in RDW.…”
Section: Discussionmentioning
confidence: 70%
“…In addition to being linked to renal function, an elevated RDW has also been associated with higher mortality in patients with CKD [9], kidney transplant recipients [25] and patients with AKI who are receiving continuous renal replacement therapy [15]. Moreover, a recent study investigated the impact of RDW on mortality in patients receiving hemodialysis and concluded that RDW may be a better predictor of mortality than hemoglobin, ferritin, and iron saturation values [12]. A similar association was noted in patients undergoing continuous ambulatory peritoneal dialysis (CAPD).…”
Section: Discussionmentioning
confidence: 99%
“…It has been linked to ischemic cerebrovascular disease and to poorer outcome after ischemic stroke [33]. Higher values of RDW have also recently shown to be associated with increased mortality of ESRD patients [34, 35]. RDW is being extensively studied and both the mechanisms linking ESRD to higher RDW, and higher RDW to cerebral ischemia and mortality are yet to be elucidated.…”
Section: Discussionmentioning
confidence: 99%